Chemical composition and antioxidant activity of tronchuda cabbage internal leaves - Ferreres, Frederico (2006)
A phytochemical study was undertaken on the internal leaves of tronchuda cabbage (Brassica oleracea L. var. costata DC). Seventeen phenolic compounds were characterized and quantified by reversed-phase HPLCDAD-ESI-MSn and HPLC/DAD, respectively: quercetin 3-O-sophoroside-7-O-glucoside, 3-p-coumaroylquinic acid, kaempferol 3-O-sophoroside-7-O-glucoside, kaempferol 3-O-(caffeoyl)-sophoroside-7-O-glucoside, sinapoyl glucoside acid, kaempferol 3-O-(sinapoyl)-sophoroside-7-Oglucoside, kaempferol 3-O-(feruloyl)-sophoroside-7-Oglucoside, kaempferol 3-O-(p-coumaroyl)-sophoroside- 7-O-glucoside, 4-p-coumaroylquinic acid, sinapic acid, kaempferol 3-O-sophoroside, 3 isomeric forms of 1,2- disinapoylgentiobiose, 1-sinapoyl-2-feruloylgentiobiose, 1,2,2-trisinapoylgentiobiose and 1,2'-disinapoyl-2-feruloylgentiobiose. Seven organic acids (aconitic, citric, ascorbic, malic, quinic, shikimic and fumaric acids) were also identified and quantified. The hot water extract of tronchuda cabbage internal leaves was investigated for its capacity to act as a scavenger of DPPH- radical and reactive oxygen species (superoxide radical, hydroxyl radical and hypochlorous acid), exhibiting antioxidant capacity in a concentration dependent manner against all radicals.